The Role of Peers on Self-Confidence in Increasing Student Learning Achievement: An Observational Study in Jambi City, Indonesia - Amelia, Laili Riski; Rosmiati; Novia Sri Dwijayanti (Arkus, 2024)
Students' self-confidence and learning achievement are two important aspects of education. This research aims to examine the role of peers in increasing students' self-confidence and learning achievement in Jambi City, Indonesia. This research uses a quantitative approach with a cross-sectional design. The research sample consisted of 350 senior high school students in Jambi City who were selected by random sampling. Data was collected through questionnaires and analyzed using structural equation modeling partial least squares (SEM-PLS). The results of SEM-PLS analysis show that peers have a positive and significant influence on students' self-confidence (β = 0.45, p < 0.001). Apart from that, self-confidence also has a positive and significant effect on student learning achievement (β = 0.38, p < 0.001). Peers also have an indirect influence on learning achievement through self-confidence. Peers play an important role in increasing students' self-confidence and learning achievement in Jambi City. Interventions involving peers can be an effective strategy to improve both aspects.